2020
DOI: 10.1002/chem.202000282
|View full text |Cite
|
Sign up to set email alerts
|

Solvophobically Driven Complexation of Adamantyl Mannoside with β‐Cyclodextrin in Water and Structured Organic Solvents

Abstract: The effects of solventa nd temperature on the complexation of adamantyl mannoside with b-cyclodextrin and 6-O-monotosyl-6-deoxy-b-cyclodextrinw ere explored experimentally and by means of molecular dynamics simulations. Efficientb inding was observedo nly in hydrogenbondeds olvents, which indicated solvophobically driven complexation. Thes tability of the inclusion complex was considerably higheri na queous media. Ap ronouncedt emperature dependence of D r H * and D r S * ,r esulting in perfect enthalpy-entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 88 publications
3
19
0
Order By: Relevance
“…Although the magnitude of Δ C p b should not be used to identify the role of the HE in the binding process, its sizable temperature dependence may be considered a more convincing evidence . With some exceptions, including cyclodextrins and cyclophanes, the effect of the temperature in the thermodynamics of the binding processes of synthetic receptors in water has not been extensively studied …”
Section: Electrostatic and Dispersion Intermolecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the magnitude of Δ C p b should not be used to identify the role of the HE in the binding process, its sizable temperature dependence may be considered a more convincing evidence . With some exceptions, including cyclodextrins and cyclophanes, the effect of the temperature in the thermodynamics of the binding processes of synthetic receptors in water has not been extensively studied …”
Section: Electrostatic and Dispersion Intermolecular Interactionsmentioning
confidence: 99%
“…Although the magnitude of ΔC p b should not be used to identify the role of the HE in the binding process, its sizable temperature dependence may be considered a more convincing evidence. 11 With some exceptions, including cyclodextrins 72 and cyclophanes, the effect of the temperature in the thermodynamics of the binding processes of synthetic receptors in water has not been extensively studied. 49 In water, the temperature dependence of enthalpy is typically reflected in parallel changes of entropy, owing to the almost temperature invariable magnitude of the free energies of binding and protein folding processes in water.…”
Section: Hydrophobic Effectmentioning
confidence: 99%
“…Moreover, to clarify the effect of the compression temperature on the mechano-responsiveness, the change in transmittance with respect to the compression temperature was evaluated. It has been reported that the association constant of the host–guest complex of β-CD and Ad in water was almost constant at different temperatures . Therefore, it is expected that the strength of the host–guest interaction itself in the hydrogels did not changed significantly in the range of the temperature from 25 to 50 °C.…”
mentioning
confidence: 94%
“…It has been reported that the association constant of the host−guest complex of β-CD and Ad in water was almost constant at different temperatures. 32 Therefore, it is expected that the strength of the host−guest interaction itself in the hydrogels did not changed significantly in the range of the temperature from 25 to 50 °C. Figure 2e shows that above the LCST, the decrease in transmittance, and the signal-to-noise ratio between the pressed and unpressed areas were more significant at higher compression temperatures (37 and 50 °C), whereas at temperatures below or around the LCST (the LCST of P(NIPAAm 95 -co-AdAAm 5 ) was 23 °C in the absence of β-CD), the transmittance was almost the same before and after compression (25 °C).…”
mentioning
confidence: 97%
“…Many literature examples exist detailing inclusion complexes of lipophilic adamantane derivatives with b-CDs, [23][24][25][26][27][28][29] but only a few examples describe the binding of larger diamondoid homologues into a bor especially g-CD cavity, which is larger and more flexible. 30 One such recent report deals with adamantane, diamantane and triamantane amines, carboxylic acids and its derivatives as suitable guests for band g-CDs.…”
Section: Introductionmentioning
confidence: 99%